Uniwersytet Zielonogórski wobec zmian rynku edukacyjnego. Analiza porównawcza dynamiki liczby kandydatów w latach 2009/2010-2013/2014 = University of Zielona Góra towards the change in the education market. A comparative analysis of the dynamics of the number of applicants in the years 2009/2010-2013/2014 - Mianowska, Edyta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article discusses the analysis of the dynamics of the number of applicants to the University of Zielona Góra in the last five years (2010-2014). The context of the analyses was set by the transformation of the higher education and demographic changes shaping the situation in the education services market at the higher level. The aim of the research was to describe the dynamics of the number of applicants to study at the University of Zielona Góra as well as to trace changes occurring in the structure of chosen characteristics of applicants and their strategies.
Keywords: Uniwersytet Zielonogórski; kształcenie uniwersyteckie; studenci; badania